2007
DOI: 10.1160/th07-04-0261
|View full text |Cite
|
Sign up to set email alerts
|

Arteriogenesis: A focus on signal transduction cascades and transcription factors

Abstract: SummaryIn recent years intensive investigations have been performed to unravel the molecular mechanisms of collateral artery growth (arteriogenesis), a process designed by nature to compensate the devastating consequences of major arterial occlusions. Currently, a variety of gene products as well as signal transduction pathways involved in arteriogenesis have been identified. However, it is still not clear how the progression of cellular signals evoked by an increased blood flow and therefore mechanical stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Abra initiates SRF-dependent transcription. Apart from previous findings of SRF-dependent transcription during arteriogenesis (reviewed in 28 ), we were able to demonstrate that SRF itself is upregulated under conditions of high FSS. RhoA-dependent regulation of the actin cytoskeleton selectively regulates SMC differentiation marker gene expression by modulating SRF dependent transcription.…”
Section: Troidl Et Almentioning
confidence: 43%
“…Abra initiates SRF-dependent transcription. Apart from previous findings of SRF-dependent transcription during arteriogenesis (reviewed in 28 ), we were able to demonstrate that SRF itself is upregulated under conditions of high FSS. RhoA-dependent regulation of the actin cytoskeleton selectively regulates SMC differentiation marker gene expression by modulating SRF dependent transcription.…”
Section: Troidl Et Almentioning
confidence: 43%
“…9 SRF as well as MRTFs are recognized as liaisons connecting the key pathways of arteriogenesis, ie, Rho pathway with downstream genes. 47 Therefore, we speculate that FHL-2 in vascular SMCs might contribute the process of atherosclerosis or angiogenesis through suppressing phenotypic switching.…”
Section: Discussionmentioning
confidence: 89%
“…The observed phenotype is similar to the effect of vegf knockdown and is not rescued by VEGF injections (39). Further evidence of a potential role for this pathway in arterial specification comes from observation of increased P-ERK expression in newly forming arterial vessels (8,41) and from a study of gridlock mutants (14). However, to our knowledge, no study to date has shown that ERK activation can promote arterial morphogenesis and branching during development and in adult tissues.…”
Section: Discussionmentioning
confidence: 69%